The genus Hyalomma Koch, 1844. VIII. Redescription of three Hyalommina Schulze, 1919 species (Acari: Ixodidae) from South Asia with notes on their biology - Apanaskevich, Dmitry A.; Horak, Ivan G.; Geevarghese, Geevarghese (Zootaxa, 2009)
The South Asian ticks Hyalomma (Hyalommina) brevipunctata Sharif, 1928, Hyalomma (Hyalommina) hussaini Sharif, 1928 and Hyalomma (Hyalommina) kumari Sharif, 1928, are morphologically fairly similar. The males can be distinguished from each other by size, color and their punctation patterns. The females are easily distinguished by the shape of the genital aperture and its preatrial fold, and they also differ in size, color and punctation patterns. The immature stages can be distinguished by the measurements of various characteristics and the ratios of these, the shape of the scutum, gnathosoma and hypostome, number of denticles on the hypostome and size of the spurs on coxae. All parasitic stages of the three species are illustrated and redescribed here. Their distributions are restricted to South Asia, although there are some records from Central Asia. Large and medium-sized ungulates are the principal hosts of the adults, whereas the immature stages infest various species of small mammals. All are three-host species. Data on their disease relationships are also provided.